Manajemen Kinerja Operator dan Dampaknya terhadap Kondisi Unit Wheel Loader Komatsu WA 200-5 di Pabrik Briket Tanjung Enim - Sarmidi; Nurbaiti; Yulius Mases; Siti Nurjanah; Indra Nuryanneti (Automotive Innovations Journal, 2026)
Wheel loaders play a crucial role in material handling operations at briquette plants, and their operational condition is strongly influenced by operator performance. Effective operator performance management, including technical competence, work discipline, compliance with standard operating procedures, and awareness of daily equipment maintenance, is essential to ensure unit reliability and service life. This study aims to analyze operator performance management and its impact on the condition of the Komatsu WA 200-5 wheel loader operating at the Tanjung Enim Briquette Plant. A descriptive quantitative research method was employed, with data collected through field observations, interviews, equipment maintenance records, and operational reports. Operator performance management was evaluated based on indicators of operating skills, procedural compliance, and responsibility for daily inspections, while unit condition was assessed using indicators such as damage frequency, breakdown occurrences, and equipment availability. The results indicate that well-implemented operator performance management has a positive impact on wheel loader condition, as reflected by reduced damage rates, lower downtime, and improved equipment availability to support production activities. These findings demonstrate that improving operator performance management not only enhances operational efficiency but also contributes to the sustainability and reliability of heavy equipment usage. Therefore, strengthening operator performance management systems is a strategic approach to maintaining equipment condition and supporting continuous production operations at briquette plants.